Design and implementation of weaving‐type pad for contactless EV inductive charging system. Issue 10 (1st October 2014) - Lee, Jia‐You; Shen, Hung‐Yu; Lee, Kun‐Wei
Abstract : The purpose of this study is to develop a new weaving‐type pad for electric vehicles (EV) contactless inductive charging system. This proposed charging pad which consists of a weaving‐type coil is fabricated to obtain a uniform mutual inductance profile over the charging surface and to solve the problem of present inductive coupled structure in which the EV has to be placed exactly on a specific place. Apart from weaving‐type pad, type E core and two overlapping coils are utilised as a secondary pickup to guide and to pick more magnetic flux. The analysis and simulation of magnetic characteristic for comparing the proposed weaving‐type pad to simple shape pad are performed by finite‐element‐analysis (FEA) software. Phase locked loop circuit is utilised to match the operating frequency and resonant frequency in order to solve the loading effect problem caused by impedance variation during the battery charging procedure. To validate the concept and system design, a laboratory scale test system with weaving‐type pad for EV contactless inductive charging is built and tested. The coupling efficiency is found to be 66% for an air gap of 9 cm between the weaving‐type charging pad and pickup when a 2 Ah lithium iron phosphate battery is charged.